Efektivitas Penerapan Metode Resitasi Terhadap Peningkatan Hasil Belajar Akidah Akhlak Siswa Kelas VIII MTs Ma’arif As-Sahro Kepil Wonosobo - Asep Sunarko; Defi Defi; Ischak Suryo Nugroho (DAS Institute, 2024)
The background to this research is that the learning methods used by teachers at MTs Ma'arif As-Sahro still tend to use traditional methods and lack variety in learning, learning is still boring and there is a lack of active participation from students. This problem has an impact on the academic achievement of students in the Aqidah Akhlak subject. This research was carried out for 2 months. Class VIII A students at MTs Ma'arif As-Sahro Kepil Wonosobo for the 2022/2023 academic year are the students involved in this research process. The findings reveal that learning Aqidah Akhlak through the use of the recitation method in this research improves learning outcomes. This confirmation is proven through the use of a strengthening test, which produces a numerical value of 0.567. The findings reveal that there is variation and improvement in student academic achievement after implementing the recitation pedagogical approach. This is proven by using the t-test tcount > ttable both at the 1% significance level, namely 2.72 > 2, 240. However, at the 5% significance level, the ttable is 2.020. In this research, the factors that support the use of the recitation method are: 1) thorough preparation, 2) students' motivation and enthusiasm for learning, 3) interesting learning methods, and 4) guidance and explanations to students. Then, the following are factors inhibiting the use of the recitation method: 1) limited time, 2) student memory, 3) differences in student achievement, and 4) lack of school facilities.